DCA Protects against Oxidation Injury Attributed to Cerebral Ischemia-Reperfusion by Regulating Glycolysis through PDK2-PDH-Nrf2 Axis - Xiaoyong Zhao (Hindawi Limited, 2021)
Cerebral ischemic stroke (IS) is still a difficult problem to be solved; energy metabolism failure is one of the main factors causing mitochondrion dysfunction and oxidation stress damage within the pathogenesis of cerebral ischemia, which produces considerable reactive oxygen species (ROS) and opens the blood-brain barrier. Dichloroacetic acid (DCA) can inhibit pyruvate dehydrogenase kinase (PDK). Moreover, DCA has been indicated with the capability of increasing mitochondrial pyruvate uptake and promoting oxidation of glucose in the course of glycolysis, thereby improving the activity of pyruvate dehydrogenase (PDH). As a result, pyruvate flow is promoted into the tricarboxylic acid cycle to expedite ATP production. DCA has a protective effect on IS and brain ischemia/reperfusion (I/R) injury, but the specific mechanism remains unclear. This study adopted a transient middle cerebral artery occlusion (MCAO) mouse model for simulating IS and I/R injury in mice. We investigated the mechanism by which DCA regulates glycolysis and protects the oxidative damage induced by I/R injury through the PDK2-PDH-Nrf2 axis. As indicated from the results of this study, DCA may improve glycolysis, reduce oxidative stress and neuronal death, damage the blood-brain barrier, and promote the recovery of oxidative metabolism through inhibiting PDK2 and activating PDH. Additionally, DCA noticeably elevated the neurological score and reduced the infarct volume, brain water content, and necrotic neurons. Moreover, as suggested from the results, DCA elevated the content of Nrf2 as well as HO-1, i.e., the downstream antioxidant proteins pertaining to Nrf2, while decreasing the damage of BBB and the degradation of tight junction proteins. To simulate the condition of hypoxia and ischemia in vitro, HBMEC cells received exposure to transient oxygen and glucose deprivation (OGD). The DCA treatment is capable of reducing the oxidative stress and blood-brain barrier of HBMEC cells after in vitro hypoxia and reperfusion (H/R). Furthermore, this study evidenced that HBMEC cells could exhibit higher susceptibility to H/R-induced oxidative stress after ML385 application, the specific inhibitor of Nrf2. Besides, the protection mediated by DCA disappeared after ML385 application. To sum up, as revealed from the mentioned results, DCA could exert the neuroprotective effect on oxidative stress and blood-brain barrier after brain I/R injury via PDK2-PDH-Nrf2 pathway activation. Accordingly, the PDK2-PDH-Nrf2 pathway may play a key role and provide a new pharmacology target in cerebral IS and I/R protection by DCA.